Effect of Microencapsulated 2(3)-Tert-Butyl-4- Hydroxyanisole (BHA) at Sub-Lethal Dose on the Growth of Aspergillus flavus and Production of Aflatoxin in Peanut Food Model System - García, Daiana (2019)
The need to ensure the microbiological quality and safety of food products has stimulated interest for new strategies avoiding the use of chemical preservatives in foods and feeds. Microencapsulated food grade antioxidants could be an alternative for control fungal contamination in foods. In this sense, the aim of our study was to examine the effect of a sub-lethal dose of microencapsulated butylated hydroxyanisole (BHA) (0.65mM) on physiological behavior of Aspergillus flavus, an aflatoxin B1 producer fungi. In this sense, we evaluated growth rate, time to growth, biomass and aflatoxin B1 accumulation of an isolate of A. flavus (RCP08108) with two water activities (0.99 and 0.96 aw) and two growth substrate (Peanut meal extract agar and peanut kernels). All fungal physiological features studied in this work (growth rate, time to growth, biomass and AFB1 accumulation), were modified by the application of the sub-lethal dose of BHA formulation, for both growth substrate and water availability. Presence of the encapsulated antioxidant showed significant change in Pearson coefficients respect to the controls for all studied parameters. As conclusion, evaluated sub-lethal dose of BHA formulation, result in a reduction on growth and toxin accumulation. Results of this work indicate the need to consider both fungal primary and secondary metabolism to determine the effect of food grade antioxidant formulation, in order to improve the production of microcapsules for application in a future in the food system.